Intelligent Control of Switched Reluctance Motor Using Fuzzy Logic and SMC Controller for EV Applications - Vijayalakshmi K; Srinivas Kn (Universitas Diponegoro, 2022)
Switched Reluctance Motors have expanded their field of application in recent years, from a control system stepping motor to high torque e-vehicle applications. High-speed operation and a light-weight driving motor are critical elements for an effective electric vehicle design. SRM's low torque-to-weight ratio and magnetless rotor design make it ideal for use in electric vehicles with less weight and low cost. The only limitation with switched reluctance motors is torque ripple and vibrations. There have been a variety of techniques to reducing torque pulsations in the SRM, by which vibration and noise can be reduced. In this paper, an optimization technique is used in switching controllers in and a comparison is done between a sliding mode controller (SMC) with a modified reaching law and by using Fuzzy Logic Controller (FLC). By using matlab Simulink the magnitude of torque ripple is simulated and compared for 8/6 pole SRM. The results shows that the torque ripple is reduced in fuzzy compared to SMC significantly.